KAPASITAS KOPERTAIS DALAM PENINGKATAN MUTU PERGURUAN TINGGI AGAMA ISLAM SWASTA (PTAIS): STUDI KASUS DI KOPERTAIS WILAYAH VIII SUMATERA BARAT: THE CAPACITY OF PRIVATE UNIVERSITY COORDINATING BODY (KOPERTAIS) IN IMPROVING THE QUALITY OF PRIVATE ISLAMIC HIGHER EDUCATION (PTAIS): A CASE STUDY IN THE REGION VIII WEST SUMATRA - Sumarsih Anwar (Penamas, 2015)
This paper presents the results of a research on the capacity of the Private University Coordinating Body (Kopertais) Region VI West Sumatra in improving the quality of Private Islamic Higher Education (Ptais) in accordance with its potential and conditions. This study uses a single case study; primary data has been obtained and collected from informants through interviews, observation and field notes. The results of the study indicate that the capacity of the Private University Coordinating Body in carrying out its duties and functions in order to improve the quality of Private Islamic Higher Education is not run properly and optimally due to various factors. The main factor was a weak juridical status which leads to the lack of resources (personnel, facilities and infrastructure) and budget. Another factor is the leadership dualism of a rector, where he is as ex officio rector and also as a coordinator Kopertais. It results in an uneffective leadership and management functions of this organization. Keywords: Private Islamic Higher Education (Ptais), quality of education, Private University Coordinating Body (Kopertais), West Sumatra Tulisan ini menyajikan hasil penelitian tentang kapasitas Koordinatoriat Perguruan Tinggi Islam (Kopertais) Wilayah VI Sumatera Barat dalam peningkatan mutu Perguruan Tinggi Agama Islam (PTAIS) sesuai dengan potensi dan kondisi yang dimilikinya. Penelitian ini menggunakan studi kasus tunggal, dengan data primernya diperoleh dan dikumpulkan secara langsung dari informan melalui wawancara, pengamatan, dan catatan lapangan. Hasil dari penelitian menunjukkan, bahwa kapasitas Kopertais dalam menjalankan tugas dan fungsi dalam rangka meningkatkan mutu PTAIS belum berjalan dengan baik dan optimal karena berbagai faktor. Faktor utamanya status yuridis yang lemah yang berakibat pada keterbatasan sumber daya (tenaga, fasilitas, dan sarana prasarana) dan anggaran. Faktor lain adalah adanya dualisme kepemimpinan, di mana Rektor secara ex officio sebagai kordinator Kopertais, berakibat fungsi kepemimpinan dan manajemen organisasi tidak efektif. Kata Kunci: PTAIS, mutu pendidikan, Kopertais, Sumatera Barat.